Reevaluating Biota Alteration: Reframing Environmental Influences on Chronic Immune Disorders and Exploring Novel Therapeutic Opportunities - Parker, William; Jirků, Kateřina; Patel, Esha; Williamson, Lauren; Anderson, Lauren; Laman, Jon D (The Yale journal of biology and medicine, 2024)
Environmental mismatches are defined as changes in the environment that induce public health crises. Well known mismatches leading to chronic disease include the availability of technologies that facilitate unhealthy diets and sedentary lifestyles, both factors that adversely affect cardiovascular health. This commentary puts these mismatches in context with biota alteration, an environmental mismatch involving hygiene-related technologies necessary for avoidance of infectious disease. Implementation of hygiene-related technologies causes a loss of symbiotic helminths and protists, profoundly affecting immune function and facilitating a variety of chronic conditions, including allergic disorders, autoimmune diseases, and several inflammation-associated neuropsychiatric conditions. Unfortunately, despite an established understanding of the biology underpinning this and other environmental mismatches, public health agencies have failed to stem the resulting tide of increased chronic disease burden. Both biomedical research and clinical practice continue to focus on an ineffective and reactive pharmaceutical-based paradigm. It is argued that the healthcare of the future could take into account the biology of today, effectively and proactively dealing with environmental mismatch and the resulting chronic disease burden.
Keywords: nemoci imunitního systému; chronická nemoc; životní prostředí; zvířata; Humans; Immune System Diseases; Allergy; Autoimmune disease; Biota alteration; History; Hygiene; Environment; lidé; Chronic Disease; Animals